Impact of simulated microgravity in short-term evolution of an RNA bacteriophage - Rodríguez-Moreno, Alicia; Martín-Blázquez, Sergio; de Heredia, Unai López; Soto, Álvaro; Lázaro, Ester (Frontiers in Microbiology, 2025)
IntroductionMicrogravity is a critical environmental factor in space that can alter microbial physiology and virus–host interactions. Understanding these effects is essential for planetary protection and crew health during long-term missions. Bacteriophage Qβ, an RNA virus infecting Escherichia coli F+ strains, provides a relevant model due to its potential presence in the human gut microbiome and its well-characterized evolutionary dynamics.MethodsWe simulated microgravity using a custom-built 3D-clinostat and compared Qβ infections in semisolid medium under standard gravity and simulated microgravity. Twelve evolutionary lines were propagated for ten serial transfers under four experimental conditions combining bacterial growth and infection environments. Viral titers were quantified by plaque assay, and consensus sequences were determined by Sanger sequencing.ResultsInitial infections under simulated microgravity yielded significantly lower viral titers than those in standard gravity, likely due to hindered phage diffusion and delayed infection initiation. After ten transfers, mutation C2011A (amino acid substitution T222N in the A1 virus protein) was fixed in all lines evolved under simulated microgravity but remained absent or polymorphic in standard gravity lines. Under simulated microgravity, the mutation increased virus titers and promoted faster initiation of infections in semisolid medium. However, those effects were not appreciable in normal gravity.DiscussionOur findings highlight the adaptability of Qβ and the potential impact of microgravity on phage-host interactions, offering insights into virus evolution in extraterrestrial conditions and its implications for space missions and planetary protection.